Analysis of the formation process and performance of magnetic Fe3O4@Poly(4-vinylpyridine) absorbent prepared by in-situ synthesis. Issue 6 (June 2018) - Zeng, Birong; Yang, Li; Zheng, Wei; Zhu, Jihong; Ma, Xiaojun; Liu, Xinyu; Yuan, Conghui; Xu, Yiting; Dai, Lizong
Abstract: The morphology evolution of the mesoporous magnetic composite nanospheres Fe3 O4 @Poly(4-vinylpyridine) during the formation process and its absorption property of Congo red were studied in this study. A simple solvothermal method was applied for the fabrication of Fe3 O4 @Poly(4-vinylpyridine) composites with regular structure and uniform size distribution in the presence of 4-vinylpyridine as the structure inducer. The morphology, structure and magnetism performance were characterized and the adsorption model and mechanism were discussed. The results showed that the Fe3 O4 @Poly(4-vinylpyridine) composites were efficient adsorbent for the removal of Congo red from water and it could be reused by a magnetic separation. The adsorption isotherm of Congo red on Fe3 O4 @Poly(4-vinylpyridine) composites was fitted well with the Langmuir adsorption model.